2014
DOI: 10.4103/2230-8229.134774
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of metabolic syndrome in a rural area of Ambala district, Haryana

Abstract: Introduction:Metabolic syndrome (MS) is a state of deranged metabolic and anthropometric status. It is considered a precursor to various cardiovascular and metabolic diseases.Objectives:(1) To determine the prevalence of MS in adults aged 20 years and above in the rural area of Ambala district, Haryana. (2) To determine the sociodemographic factors associated with MS.Materials and Methods:In a community-based cross-sectional study, a total of 1200 subjects aged 20 years and above were studied, using multi-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…In addition to the routine risk factors reported in the previous research,[ 5 11 12 13 14 15 16 ] we found that the use of refined oil for cooking and perceived stress was the significant risk factors for MS. These factors were not routinely studied earlier.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition to the routine risk factors reported in the previous research,[ 5 11 12 13 14 15 16 ] we found that the use of refined oil for cooking and perceived stress was the significant risk factors for MS. These factors were not routinely studied earlier.…”
Section: Discussionsupporting
confidence: 67%
“…[ 11 12 13 ] In India, it ranged from 9.2% to 43.2% as reported in the previous studies,[ 5 14 15 16 ] with a minimum prevalence of 9.2% and the maximum of 36%. [ 5 14 ] The variations in prevalence could be attributed to the adoption of different criteria for MS, study settings, laboratory techniques, and risk factors. Notably, in this study, the prevalence of MS was the highest among the previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…I have read a recent publication entitled “an epidemiological study of metabolic syndrome (MS) in a rural area of Ambala District, Haryana”, and would like to comment on certain issues. [ 1 ] The prevalence of MS as found in the study was 9.2%. MS is a cluster of cardiovascular risk factors.…”
mentioning
confidence: 65%
“…A limitation of this study was that the subjects’ precise occupations were unclear. As past studies have suggested, occupational factors affect the prevalence of metabolic syndrome and its components, which, for example, increases in workers whose work is sedentary [ 22 ]. Future studies should be designed to include such occupational factors as subcategories to business category.…”
Section: Discussionmentioning
confidence: 99%